2014
DOI: 10.1177/0333102414523338
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported neck pain is associated with migraine but not with tension-type headache in adolescents

Abstract: Neck pain is associated with migraine but not with tension-type headache. A possible link between migraine and neck pain may be the cervico-trigeminal convergence of neck and meningeal sensory afferents or a disturbed descending inhibition in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 34 publications
1
27
0
10
Order By: Relevance
“…In recent studies, a number of risk factors for headache and headache chronification have been identified [1][2][3][4][5][6][7][8][9][10][11][12]. Some of these risk factors are potentially amenable to interventions, such as consumption of coffee, caffeine-containing soft drinks and alcohol, smoking, physical inactivity, stress and muscular pain in the neck and shoulder region.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a number of risk factors for headache and headache chronification have been identified [1][2][3][4][5][6][7][8][9][10][11][12]. Some of these risk factors are potentially amenable to interventions, such as consumption of coffee, caffeine-containing soft drinks and alcohol, smoking, physical inactivity, stress and muscular pain in the neck and shoulder region.…”
Section: Introductionmentioning
confidence: 99%
“…Erwachsene Patienten mit kombinierter Migräne und KST, aber auch mit alleinigem KST oder Migräne haben gehäuft Nackenschmerzen (89,3, 88,4 und 76,2 %) [30]. Dieser Befund konnte für KST in einer Gruppe Jugendlicher nicht bestätigt werden [31]. Patienten mit KST leiden häufiger unter einer Beeinträchtigung des Schlafes i. S. von Tagesmüdigkeit, reduzierter subjektiver Schlafqualität sowie verändertem Schlafmuster bei normaler Schlafdauer.…”
unclassified
“…In epidemiologischen Studien wurden eine Reihe von Risikofaktoren für Kopfschmerzen identifiziert: Einerseits finden sich "nicht beeinflussbaren" Risikofaktoren wie genetische Ursachen und das Geschlecht (7). Andererseits bestehen neben solchen nicht beeinflussbaren Risikofaktoren auch beeinflussbare Risikofaktoren wie Stress, erhöhte muskuläre Anspannung und Schmerzen in der Schulter-und Nackenregion, und "Lifestyle Faktoren" wie Rauchen, hoher Koffein-und Alkoholkonsum und körperliche Inaktivität (8)(9)(10)(11). Durch ein theoretisches "vollständiges" Vermeiden dieser beeinflussbaren Risikofaktoren könnten etwa 19,7% der Kopfschmerzen und sogar 43,8% von Migräneanfälle verhindert werden (12).…”
unclassified